Fantastic optical illusions. (New York : DK, Penguin Random House, 2017)
An exploration of optical illusions, with instructions for making them, information on how they work, and more.
6.2
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Optical illusions -- Juvenile literature; Optical illusions